2011
DOI: 10.1063/1.3525557
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial tunnel barrier gives broadband microwave transmission

Abstract: Effective properties of split-ring resonator metamaterials using measured scattering parameters: Effect of gap orientation J. Appl. Phys. 100, 034910 (2006) A simple structure comprising a metal mesh, symmetrically surrounded by subwavelength thickness dielectric layers, is shown to give near total microwave transmission over a broad frequency range. The mesh may be considered to be a tunnel barrier since it behaves as an ideal plasmonic metamaterial with a negative effective permittivity and no loss. The intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…In the mentioned models, the constitutive parameters can be arranged to be simultaneously negative below the electric and/or magnetic plasma frequency. Accordingly, these models can theoretically be used to designate a metamaterial (MTM) system (including multilayer MTM structure) for creating/realizing new functional devices [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Additionally, the Lorentz and Drude models as MTMs have been utilized in many studies in which one of them is the multilayer MTM system with the application of EM filters [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mentioned models, the constitutive parameters can be arranged to be simultaneously negative below the electric and/or magnetic plasma frequency. Accordingly, these models can theoretically be used to designate a metamaterial (MTM) system (including multilayer MTM structure) for creating/realizing new functional devices [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Additionally, the Lorentz and Drude models as MTMs have been utilized in many studies in which one of them is the multilayer MTM system with the application of EM filters [12].…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between the conventional and MTM structures based on the length sensitivity and impedance mismatch was discussed by B. Edwarset et al [9]. Furthermore, polarization independent tunneling according to the phase and impedance matching [10] and broadband tunneling based on the constitutive parameters [11] can be given as sample studies in the framework of the wave tunneling with MTM structure(s). Moreover, there are recently some studies about the characterizations of multilayer MTMs for very high frequencies namely optical and terahertz frequency ranges [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As with other experiments [27,28], modeling can also be used to visualize the electric field distribution in each mode. Plots of the norm of the electric field as a function of the distance through the sample are displayed in Fig.…”
Section: Photonic Analogmentioning
confidence: 99%
“…Electromagnetic waves propagation in different plasma and plasmalike structures, in particular, transmission through nonuniform plasma have been studied by numerous research groups [1,[9][10][11][12][13][14][15][16] by different methods. In particular, it was shown that the process of the Raman scattering of a pump electromagnetic wave on Langmuir oscillations produced by the signal wave can be effective as a mechanism of information transfer through a nonuniform plasma layer [17].…”
mentioning
confidence: 99%